Pendampingan Pengembangan Modul Ajar Pada Kurikulum Merdeka di Sekolah Dasar Islam Azzihad Terpadu Bandung - Marwan, Iwan; Sunaiyah, Salma; Candra, Monica Septya Kartika; lfiyani, Rizqiyah (Universitas Nusantara PGRI Kediri, 2025)
The characteristics of Kurikulum Merdeka contain learning outcomes per phase that support the flexibility of educators and education units to develop quality curriculum and learning according to the potential and local wisdom of the school environment, so that assistance in developing teaching modules for Kurikulum Merdeka at the Bandung Integrated Azzihad Islamic Elementary School is very necessary and important to implement. This service program uses Asset Based Community Development (ABCD) by referring to the theory of McKnight and Kretzmann (1993). The service activity of assisting the preparation of teaching modules at SDIT Azzihad Bandung has been successfully implemented as evidenced by the increasing ability of teachers to develop teaching modules. The results of this activity exceeded the 1% assumption. The teachers actively participated in the activity from the beginning to the end of the activity. Based on the above conclusions, it can be said that the service activities for preparing teaching modules for Kurikulum Merdeka at SDIT Azzihad Bandung have a significant impact.